There are different ways to solve this:
Substitution:
in the equation: y = 2x + 3 every time you see a y insert -x in its place. This will solve for the x of the intersect
-x = 2x + 3
(-x-2x) = (2x - 2x) + 3
![(-3x)/(-3) = (3)/(-3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/c91f15cirgr9562n7l33irgvzzv3taigyo.png)
x = - 1
to solve for y incert x which is -1 into the equation y = 2x + 3
y = 2(-1) + 3
y = -2 + 3
y = 1
(-1,1)
Hope this helped! Let me know if you want the other methods of solving this explained as well!